2012
DOI: 10.1159/000342811
|View full text |Cite
|
Sign up to set email alerts
|

Early Development of Secondary Hyperparathyroidism following Renal Transplantation

Abstract: Background: Optimal levels of intact parathyroid hormone (iPTH) in the post-transplant period are not known due to insufficient data. Therefore, we aimed to describe secondary hyperparathyroidism (SHPT) in Swedish renal transplant (RT) recipients and also report events of fractures and vascular events potentially related to levels of iPTH. Methods: Medical charts from 132 RT recipients were retrospectively reviewed. Laboratory/clinical data were obtained at regular points up to 12 months post RT. Three groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Levels of parathyroid hormone (PTH) are mainly used to grade the extent of sHPT and both high and low PTH have been associated with cardiovascular disease (CVD) in patients on maintenance dialysis [ 3 6 ]. Renal transplantation improves many of the underlying causes of sHPT and levels of PTH decrease after transplantation, even though sHPT persists in the majority of renal transplant recipients over the short as well as long term [ 7 , 8 ]. Recent studies have shown no association between post-transplant PTH and risk of vascular events [ 9 ], but have shown an association with graft failure and mortality [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Levels of parathyroid hormone (PTH) are mainly used to grade the extent of sHPT and both high and low PTH have been associated with cardiovascular disease (CVD) in patients on maintenance dialysis [ 3 6 ]. Renal transplantation improves many of the underlying causes of sHPT and levels of PTH decrease after transplantation, even though sHPT persists in the majority of renal transplant recipients over the short as well as long term [ 7 , 8 ]. Recent studies have shown no association between post-transplant PTH and risk of vascular events [ 9 ], but have shown an association with graft failure and mortality [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kidney transplantation rapidly restores GFR and the renal capacity to respond to PTH (that is, phosphaturia and tubular calcium reabsorption). 8,9 Usually, some degree of autoregulation is preserved with progressive PTH reduction and regression of parathyroid hyperplasia a few months after transplantation. However, in 20%-30% of patients, parathyroid gland resistance to inhibitory feedback persisted several years after transplantation, 9 and inappropriately high PTH levels are associated with hypercalcemia, hypophosphatemia, renal allograft calcifications and dysfunction, loss of bone mineral density (BMD) and increased risk of fracture, vascular calcification, and increased risk of cardiovascular events.…”
mentioning
confidence: 99%
“…Levels of PTH accumulate during ESRD thus a rapid decrease in PTH is seen immediately after transplantation. Thereafter, levels of PTH keep decreasing slowly and stabilize after the first 6 months (Isaksson & Sterner 2012). The majority of patients have PTH levels above the reference range 1 year after transplantation (Sprague et al 2008).…”
Section: Renal Transplantationmentioning
confidence: 98%